PERENCANAAN STRATEGIS SISTEM INFORMASI UNTUK MENINGKATKAN PELAYANAN PADA MASYARAKAT MENGGUNAKAN METODE WARD AND PEPPARD (STUDI KASUS: KANTOR PERTANAHAN KABUPATEN X) - Rohman Sukarya, Robby (INFOKOM (Informatika & Komputer), 2025)
This research aims to develop a strategic information system (IS) planning document at the Land Office of West Bandung Regency using the Ward and Peppard methodology. The study applies a qualitative approach, collecting data through interviews, document studies, and observations. The analysis includes SWOT, Value Chain, McFarlan Strategic Grid, and business and IS/IT environmental analysis. The result is an integrated IS strategy, IT strategy, and IS/IT management strategy to enhance public service delivery. The outcome provides a practical IS master plan that aligns with institutional vision, mission, and future needs.